Properties of Permutation Groups Using Wreath Product - Terna, Achaku David; Omini, Abam Ayeni (International Journal of Mathematical Research, 2016)
Classification of the p-subgroups of the finite group of order 12 was done using Cauchy’s Lagrange’s and Sylow’s Theorems up to Isomorphism subgroups and related to the Dihedral group of order 20 (D2n) in Chemical Bonding.